Searching for processes with invisible particles using a matrix element-based method - Ferreira de Lima, Danilo Enoque; Mattelaer, Olivier; Spannowsky, Michael (Physics letters, 2018)
We propose a fully flexible method to discriminate between signal and background using a matrix element-based method in the presence of multiple invisible particles. The proposed method performs a mapping of the measured final state onto an observable which improves the separation between signal and background using their matrix elements. To show how performant this generic method is in separating signal from background, we apply it to the prominent partly invisible decay of a Higgs boson into a muon-antimuon pair and two muon-neutrinos via two W bosons.